2019
DOI: 10.1016/j.eurpsy.2019.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Subjective response to antipsychotics in bipolar disorders: A review of a neglected area

Abstract: Background: The term “subjective response to antipsychotic” (SRA) refers to changes in the subjective state experienced due to antipsychotic (AP) exposition that is independent of the therapeutic or physical side effects of these drugs. This dimension of analysis has been extensively explored in schizophrenic disorders, finding that negative SRA is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
2
0
3
Order By: Relevance
“…Una persona afectada por TB pasa tres veces más tiempo sufriendo síntomas anímicos subsindrómicos interepisódicos (especialmente depresivos) que experimentando episodios agudos (Judd et al, 2003). Sumado a esto, el tiempo que una persona sufre síntomas depresivos subsindrómicos se correlaciona estrechamente con la capacidad de que vuelva a tener una vida plena y funcional (Keck et al, 1998;Burdick et al, 2022), mientras que la intensidad de los episodios no (Strejilevich et al, 2013). Aun luego de controlados los episodios, las personas afectadas por TB continúan experimentando fluctuaciones anímicas subsindrómicas (Bonsall et al, 2012), las que se correlacionan estrechamente con el nivel de recuperación funcional (Strejilevich et al, 2013;Szmulewicz et al, 2019).…”
Section: El Litio Y El Concepto Clínicoterapéutico De Los Tbunclassified
See 2 more Smart Citations
“…Una persona afectada por TB pasa tres veces más tiempo sufriendo síntomas anímicos subsindrómicos interepisódicos (especialmente depresivos) que experimentando episodios agudos (Judd et al, 2003). Sumado a esto, el tiempo que una persona sufre síntomas depresivos subsindrómicos se correlaciona estrechamente con la capacidad de que vuelva a tener una vida plena y funcional (Keck et al, 1998;Burdick et al, 2022), mientras que la intensidad de los episodios no (Strejilevich et al, 2013). Aun luego de controlados los episodios, las personas afectadas por TB continúan experimentando fluctuaciones anímicas subsindrómicas (Bonsall et al, 2012), las que se correlacionan estrechamente con el nivel de recuperación funcional (Strejilevich et al, 2013;Szmulewicz et al, 2019).…”
Section: El Litio Y El Concepto Clínicoterapéutico De Los Tbunclassified
“…Sumado a esto, el tiempo que una persona sufre síntomas depresivos subsindrómicos se correlaciona estrechamente con la capacidad de que vuelva a tener una vida plena y funcional (Keck et al, 1998;Burdick et al, 2022), mientras que la intensidad de los episodios no (Strejilevich et al, 2013). Aun luego de controlados los episodios, las personas afectadas por TB continúan experimentando fluctuaciones anímicas subsindrómicas (Bonsall et al, 2012), las que se correlacionan estrechamente con el nivel de recuperación funcional (Strejilevich et al, 2013;Szmulewicz et al, 2019). Además, más del 40 % de las personas afectadas por TB presentan disfunciones cognitivas que persisten aún luego de controlados los episodios y los síntomas subsindrómicos de la enfermedad (Ehrlich et al, 2022).…”
Section: El Litio Y El Concepto Clínicoterapéutico De Los Tbunclassified
See 1 more Smart Citation
“…No information was available about the patient perspective on taking atypical antipsychotics or other psychiatric drugs. Some patients feel uneasy about taking antipsychotics, for reasons including stigma, side effects such as weight gain, experiencing changes to the subjective state, and concerns about long-term use [48][49][50][51]. Financial considerations and the costs of psychiatric drugs were not considered.…”
Section: Limitationsmentioning
confidence: 99%
“…An alternative way to find the optimal AD for a given patient could be found in the users' opinions and experiences while receiving these drugs. Prior research has shown that inquiry about the subjective experiences of consumers is a valid way to predict adherence and other outcomes in both schizophrenia and mood disorders (for a revision see Strejilevich et al, 2019). On the other hand, exploring users' experiences and opinions is useful to highlight clinical or adverse effects not routinely evaluated.…”
Section: Introductionmentioning
confidence: 99%